Inquiry of supersymmetric theories at LHC and a future higher energy hadron collider with the study of events containing a monojet. - Κάντα, Δήμητρα (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Εφαρμοσμένων Μαθηματικών και Φυσικών Επιστημών, 2014)
In the 20th century an important model to understand and describe the microworld and the universe was developed: The Standard Model. Experiments over the last decades have been a success for SM due to its precision in the results and its accurate predictions. However a big question remained: Why do particles have mass? The Higgs mechanism tries to give an answer to that question and its recent discovery at the LHC gave a new breath to the model. The SM might be the best model we have but it appears that it is incomplete. Experimental astronomical data suggest the existence of an unknown matter. That is dark matter (DM) and is calculated to be about 26% of the matter in our universe. Additionally theoretical issues, like strong CP problem and hierarchy problem, suggest the existence of new physics. One very promising theory beyond the SM is Supersymmetry (SUSY), a theory that extends spacetime, doubles the SM particles and could amongst other give a solution to what dark matter is. The thesis presents an analysis to find SUSY, based on the pMSSM model with a monojet and missing energy final state. In Chapter 1 we demonstrate an introduction to the standard model and its basic formalism. Chapter 2 presents an introduction to theories beyond the standard model, most importantly SUSY and its formalism. In Chapter 3 there is a description of the LHC accelerator and CMS detector as well as their electronics. In the following Chapters, 4 and 5, we describe the simulation of events with Monte Carlo generators and the selection of our events. Finally there is a presentation of our results and a synopsis of the thesis.